2015
DOI: 10.1093/scan/nsv075
|View full text |Cite
|
Sign up to set email alerts
|

The dual nature of eye contact: to see and to be seen

Abstract: Previous research has shown that physiological arousal and attentional responses to eye contact are modulated by one's knowledge of whether they are seen by another person. Recently it was shown that this 'eye contact effect' can be elicited without seeing another person's eyes at all. We aimed to investigate whether the eye contact effect is actually triggered by the mere knowledge of being seen by another individual, i.e. even in a condition when the perceiver does not see the other person at all. We measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 38 publications
4
38
2
Order By: Relevance
“…Complying with the results from the measures of autonomic arousal, the subjective measures of social presence and affective arousal and valence did not differ between the mentalizing conditions. Compared with results from previous studies showing an increase in subjective measures when believing being seen vs. not being seen by another live person (Myllyneva & Hietanen, , ), this result adds up to the idea that the same mentalizing processes are not initiated in eye contact with a person appearing in a video as compared to eye contact with a live person. It seems that the autonomic and subjective responses to eye contact depend on appropriate mentalizing processes – those reflecting the automatic contextual knowledge about being seen by another person.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Complying with the results from the measures of autonomic arousal, the subjective measures of social presence and affective arousal and valence did not differ between the mentalizing conditions. Compared with results from previous studies showing an increase in subjective measures when believing being seen vs. not being seen by another live person (Myllyneva & Hietanen, , ), this result adds up to the idea that the same mentalizing processes are not initiated in eye contact with a person appearing in a video as compared to eye contact with a live person. It seems that the autonomic and subjective responses to eye contact depend on appropriate mentalizing processes – those reflecting the automatic contextual knowledge about being seen by another person.…”
Section: Discussioncontrasting
confidence: 43%
“…Thus, the study provided strong evidence that the essential factor underlying the increased responses to eye contact was the knowledge of being seen by another person. In another study, it was further investigated whether the mere belief of being seen by another person is sufficient to trigger the enhanced response even when the viewer does not see the other person at all, or whether these responses are intimately tied to seeing the other person during the eye contact (Myllyneva & Hietanen, ). Despite heightened self‐awareness – attesting of differences in higher‐order cognition – the belief of being seen by itself did not elicit corresponding physiological responses in the absence of any visual information about the other person.…”
Section: Introductionmentioning
confidence: 99%
“…Being observed leads to cardiovascular changes, with increases in stress response when being observed during an difficult task and decreases when being observed an easy task (Blascovich et al 1999). In fact, direct gaze from a real person leads to changes in skin conductance response compared to conditions without direct gaze (Myllyneva and Hietanen 2015a). Changes in arousal from direct gaze may also account for performance in a memory task (Helminen et al 2015).…”
Section: The Audience Effect In Typical Populationsmentioning
confidence: 99%
“…Eye-to-eye contact in natural situations, however, also includes additional features such as dynamic and rapid perception of eye movements, interpretation of facial expressions, as well as appreciation of context and social conditions (Myllyneva & Hietanen, 2015; 2016; and Teufel et al, 2009). A hyperscanning (simultaneous imaging of two individuals) study using fMRI and two separate scanners has shown that responses to eye movement cues can be distinguished from object movement cues, and that partner-to-partner signal synchrony is increased during joint eye tasks (Saito et al, 2010), consistent with enhanced sensitivity to dynamic properties of eyes.…”
Section: Introductionmentioning
confidence: 99%
“…A hyperscanning (simultaneous imaging of two individuals) study using fMRI and two separate scanners has shown that responses to eye movement cues can be distinguished from object movement cues, and that partner-to-partner signal synchrony is increased during joint eye tasks (Saito et al, 2010), consistent with enhanced sensitivity to dynamic properties of eyes. Further insight into the social and emotional processing streams stimulated by eye contact originates from behavioral studies where cognitive appraisal of pictured eye-gaze directions has been shown to be modulated by social context (Teufel et al, 2009), and neural responses recorded by electroencephalography, EEG, were found to be amplified during perceptions of being seen by others (Myllyneva & Hietanen, 2016). Modulation of EEG signals has also been associated with viewing actual faces compared to pictured faces and found to be dependent upon both social attributions and the direction of the gaze (Myllyneva & Hietanen, 2015).…”
Section: Introductionmentioning
confidence: 99%